Long-Term Sustainability of Improved Sanitation in Rural Bangladesh - Hanchett, Suzanne; Krieger, Laurie; Kahn, Mohidul Hoque; Kullmann, Craig; Ahmed, Rokeya (World Bank, Washington, DC, 2014)
Sanitation needs are significant in Bangladesh, which is the most densely populated country in the world and one of the poorest. Adding to the challenge, about one-third of Bangladesh experiences annual floods and other parts of the country suffer seasonal water shortages. All of these factors have implications for the ability of rural Bangladeshis to construct and maintain latrines. Improving sanitation is a high priority national policy goal in Bangladesh. The goal of this study is to provide the Government of Bangladesh (GoB) and it's in country partners with evidence on what makes sanitation behaviors, facilities, related benefits, and programs sustainable in the Bangladesh context. The study focused on five specific objectives: determine the current status of latrine facilities built pre-and post-(Open Defecation-Free) ODF declaration and sanitation practices; understand the perceived benefits to households and communities from community-wide ODF approaches since declaring ODF status; understand whether programmatic inputs from local and national governments and civil society sanitation programs had been sustained to support communities in maintaining their ODF status and helping the poor obtain access to latrines; understand how the growth or attrition of sanitation products and services has affected the sustainability of sanitation behaviors and facilities and ODF status; and most importantly, understand why households and communities had or had not sustained improved sanitation behaviors since ODF declaration.